Mathematical Model To Identify Heavy Metal In Irrigation Channel From Cicabe Final Disposal Site - Elsa Try Julita Sembiring; Idris Maxdoni Kamil (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2018)
Aim: This study has been done to investigate the contamination in the main open channel using mathematical modeling to describe the pollutant transport of groundwater around the Cicabe final disposal site, Mandalajati Village, Bandung (coordinate 6°53'50"S; 107°39'48"E). Methodology and Result: This research was conducted in the irrigation channel that crossed next to Cicabe former waste disposal site. Pollutant parameter studied was Chromium (Cr) in water and sediment. To determine the pollutant transport along flow was using the equation of 1-dimensional analytical model based on advection–dispersion phenomena. The sampling was done twice for model calibration and validation. The samples collected included sediment and water. Pollutant input generated from leachate, domestic waste, and the open channel. The Cr simulation for k = 3 x 10-4/sec resulted that the model concentration was quite valid to approach observed Cr in observation and calibration. Simulations also done each segment to approach Cr observation with k1 = 2.5x10-4/sec, k2 = 1.1 x 10-3/sec, and k3 = 0/sec. Conclusion, significance and impact study: Cr concentration in the water met the quality standard according to PP 82/2011, while the Cr concentrations in sediment were above the US-EPA standard (2004). The simulation result for calibration and validation with k=1.4x10-4 Cr/sec showed the model was sufficient approaching the observed Cr. The Cr simulation indicated that the Cr had decayed as evidenced by the quite high Cr concentration in sediment.